Acute renal failure due to IgA nephropathy in sarcoidosis (Iranian Journal of Kidney Diseases, 2019)
Sarcoidosis is a systemic disorder affecting multiple organs. We presented a 56-year-old woman with renal impairment who was diagnosed with sarcoidosis accompanied by IgA nephropathy. Treatment with methylprednisolone was started for the patient. After treatment, the patient was discharged with good general condition and resolved proteinuria